Comparative Study Strategy of Women Cigarette Factory Workers in Formal and Informal Industry Meets the Needs of Household Economics (Case In Women Workers of PT. HM. Sampoerna Tbk. And Cigarette Manufacturing Industry Household Suwayuwo Village, Sukorejo District, Pasuruan) - Tyas Wening Puji Lestari; Yayuk Yuliati; Umu Hilmy (Program Pascasarjana Universitas Brawijaya, 2015)
Low family economy forcing women to carry out productive activities outside the home both agriculture and non-agriculture, which is in a cigarette factory. The women working as workers in the cigarette factory is part of the productive role that should be run in addition to reproductive and social role. This research was conducted with the theme Comparative Study Strategy of Women Cigarette Factory Workers in Formal and Informal Industry Meets Needs Household Economics. Researchers intend to explore deeper behind the reasons that cause women decide to work in a cigarette factory, what role do women worker, as well as the comparison of strategy women cigarette factory workers formal and informal industry in meeting the needs of the household economy. This study is denote insight of gender by using a qualitative approach with the method of collecting data through observation, documentation, in-depth interviews, and Group Interview (GI). Data were analyzed using descriptive analysis method qualitative and gender analysis using the Harvard Model Analysis. The results of this study identified that the boost increasing economic need, to improve the social status in the community, and spend leisure time are some of the reasons that cause women decide to work in a cigarette factory. Comparative analysis towards strategy of women cigarette factory workers formal and informal industry can be seen at working time, wages, health insurance, social status in the community, and work rules.